Basic diagnostic strategies in children’s anemia - Pleskaczyńska, Agata; Dobrzańska, Anna (Przewodnik Lekarza/Guide for GPs, 2008)
There are many new potential markers, which may be used in clinical hematological practice. However, these markers (e.g. transferrin, soluble transferrin receptor, ferritin) are expensive, so they are not commonly used in outpatient clinics. The aim of the paper is to discuss the pathophysiology of erythropoiesis and anaemia in children and current diagnostic strategies. Authors describe how much can be determined from the full blood count with few further biochemical investigations to identify the majority of causes of anaemia.